Perception of Business Educators and Students on Curriculum Implementation in Junior Secondary Schools in Adamawa State, Nigeria - Buba, Muhammed Modibbo (International Business Education Journal, 2020)
This study aims to determine the perception of business educators and students on curriculum implementation in junior secondary schools in Adamawa state. The descriptive co-relational study design was adopted. The population of the study was 260 teachers and 384 students who were drawn by using simple random sampling technique from junior secondary schools across the five educational zones in Adamawa State. A structured questionnaire of 25 items was used to collect data, and the data collected were analysed using descriptive statistics and Pearson Product Moment Correlation. The study found a significant relationship between the methods of teaching business studies and students’ academic performance. Moreover, there was also a significant relationship between the quality/quantity of manpower and students’ academic performance. This study recommends teachers to attend in-service training, workshops, and seminars to update their knowledge on the new curriculum being designed. Additionally, the state government should engage the services of more business educators in the state as a matter of urgency.